Differentiation of air temperature inside an urban park on the example of the Polish Aviators’ Park (Park Lotników Polskich) in Cracow - Wrona, Katarzyna (Acta Geographica Lodziensia, 2023)
Differentiation of air temperature within urban green areas is an issue relatively rarely discussed in the literature. The aim of this study was to partially fill this research gap by taking our own measurements of the local climate inside the Polish Aviators’ Park (Park Lotników Polskich) in Cracow. Measurement data regarding air temperature was collected at five points located inside the park and one in the park’s immediate vicinity. The sample period comprised of 18 days with high radiation and insolation and 12 days with a significant degree of cloud cover and weak wind, from May to September 2020. The results show that the interior of the park, where denser tree cover is present, differs in terms of microclimate from the exterior of the park, where low vegetation prevails. On sunny days, the air temperature differences were estimated to be on average 1 °C between the reference site (outside the park) and high vegetation and about 0.5 °C between the reference site and low vegetation. During the day, a greater thermal difference was noted between the park and its surroundings, while at night the contrasts became more pronounced within the park itself due to the intense cooling of the exposed grassy areas.